2002
DOI: 10.1111/j.1749-6632.2002.tb03013.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I and Class II Association with Ankylosing Spondylitis in a Southern Indian Population

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory condition associated with HLA B27. But the association is not absolute. Hence association with other HLA class I antigens and class II alleles was studied in a southern Indian population. Sixty‐five patients with primary AS were typed serologically for HLA class I antigens. Age‐ and sex‐matched disease controls (37 with enterogenic reactive arthritis [ReA] and 25 with undifferentiated spondyloarthropathy [UnSpA]) and 124 healthy controls were studied. PCR‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…Ten Egyptian patients were tested in our study and the result was positive in 9 of them (90%), which is still within the worldwide figure but much higher than the data from Egypt (58.6%) [11]. Our study included the Asian population also, and, among 26 Indians, 73% were HLA-B27 positive, this is close to the frequency reported among Indians in studies done in the Middle East and India [9, 17]. …”
Section: Discussionsupporting
confidence: 72%
“…Ten Egyptian patients were tested in our study and the result was positive in 9 of them (90%), which is still within the worldwide figure but much higher than the data from Egypt (58.6%) [11]. Our study included the Asian population also, and, among 26 Indians, 73% were HLA-B27 positive, this is close to the frequency reported among Indians in studies done in the Middle East and India [9, 17]. …”
Section: Discussionsupporting
confidence: 72%
“…Uveitis, FMF and Betcet' disease are called the non-classified spondyloarthropathies. Since the 1970s, it has been shown that HLA-B27 is remarkably associated with the disease (6,7,(28)(29)(30). In our study, we found statistically significant HLA-B27 in both group.…”
Section: Discussionsupporting
confidence: 63%
“…However, in the SpA patient group we observe a significant positive association of HLA-B27 and Cw‫.20ء‬ The significant association of Cw‫20ء‬ with SpA has been identified for the first time in the Kerala population. The Cw‫20ء‬ association with SpA has been reported earlier from a different cohort of South Indian samples from Chennai [22]. As this haplotype of B‫72ء‬ and Cw‫20ء‬ is significantly high in the SpA patients of South Indian origin, this suggests that these alleles are in strong linkage disequilibrium in South India.…”
Section: Discussionmentioning
confidence: 61%